Efficacy and safety of once‐weekly dulaglutide in combination with sulphonylurea and/or biguanide compared with once‐daily insulin glargine in Japanese patients with type 2 diabetes: a randomized, open‐label, phase III, non‐inferiority study. Issue 10 (20th August 2015) - Araki, E.; Inagaki, N.; Tanizawa, Y.; Oura, T.; Takeuchi, M.; Imaoka, T.
<x xml:space="preserve">Abstract</x> Aims To evaluate 0.75 mg of dulaglutide, a once‐weekly glucagon‐like peptide‐1 receptor agonist, compared with once‐daily insulin glargine for glycaemic control in Japanese patients with type 2 diabetes (T2D). Methods In this phase III, randomized, open‐label, parallel‐group, 26‐week study, 361 patients with inadequately controlled T2D receiving sulphonylureas and/or biguanides, aged ≥20 years, with glycated haemoglobin (HbA1c) levels 7.0–10.0% (53–86 mmol/mol), inclusive, were randomized (1 : 1) to receive dulaglutide or glargine. Participants and investigators were not masked to treatment allocation. The primary measure was change from baseline in HbA1c at 26 weeks, analysed using a mixed‐effects model for repeated measures, with a predefined non‐inferiority margin of 0.4%. Results At week 26, least‐squares (LS) mean (standard error) reductions in HbA1c were −1.44 (0.05)% [−15.74 (0.55) mmol/mol] in the dulaglutide group and −0.90 (0.05)% [−9.84 (0.55) mmol/mol] in the glargine group. The mean between‐group treatment difference in HbA1c was −0.54% (95% CI −0.67, −0.41) [−5.90 mmol/mol (95% CI −7.32, −4.48)]; p < 0.001. Dulaglutide significantly reduced body weight compared with glargine at week 26 (LS mean difference −1.42 kg, 95% CI −1.89, −0.94; p < 0.001). The most frequent adverse events with dulaglutide treatment were nasopharyngitis and gastrointestinal symptoms. The incidence of hypoglycaemia was significantly lower with dulaglutide [47/181 (26%)] compared with glargine [86/180 (48%)], p < 0.001. Conclusion In Japanese patients with T2D uncontrolled on sulphonylureas and/or biguanides, once‐weekly dulaglutide was superior to once‐daily glargine for reduction in HbA1c at 26 weeks. Although dulaglutide increased gastrointestinal symptoms, it was well tolerated, with an acceptable safety profile.